A Biomicrofluidic Screening Platform for Dysfunctional Endothelium‐Targeted Nanoparticles and Therapeutics. Issue 1 (4th December 2021) - Bazban-Shotorbani, Salime; Gavins, Felicity; Kant, Krishna; Dufva, Martin; Kamaly, Nazila
Abstract : The internal surfaces of all blood and lymphatic vessels are lined with an endothelium, which tightly controls and regulates the permeability of biological molecules. A dysfunctional endothelium (Dys‐En) is a hallmark of many diseases, including atherosclerosis. Dys‐En in atherosclerosis leads to loss of adherens junctions between cells, thus enhancing permeability and upregulation of adhesion receptors such as vascular cell adhesion molecule 1 (VCAM‐1). Both this enhanced permeability of the endothelium and associated upregulated endothelial cell surface receptors can be exploited in nanomedicine targeting to atherosclerotic plaques. However, the relationship between targeting ligand and nanoparticle (NP) size is not well understood within this context. Herein, a biomicrofluidic model of Dys‐En is developed and this platform is used to screen VCAM‐1 targeted NPs. Screening of NPs with varying properties under flow shows that size plays a dominant role in NP targeting, with NPs in the range of 30–60 nm showing increased targeting to Dys‐En. Moreover, treatment of Dys‐En‐on‐a‐chip with Annexin A1, as a novel proresolving mediator of inflammation, results in restoration of adherens junctions and normalization of the barrier integrity. The results demonstrate utility of using "Dys‐En‐on‐a‐chip" as a screening platform for Dys‐En‐targeted nanomedicines and biologics. Abstract : In an atherosclerotic vessel, neovasculatures (i.e., new vessels) sprout into plaques. The endothelium of these neovessels is inflamed and dysfunctional, which is the initial hallmark of atherosclerosis. Herein, a biomimetic model of dysfunctional endothelium is developed using a small microfluidic chip. Then, developed dysfunctional‐endothelium‐on‐a‐chip is recruited as a screening platform for antiatherosclerotic biologics and targeted nanoparticles.